2011
DOI: 10.22610/jsds.v1i5.645
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Enterprise Risk Management (ERM) Practices in Malaysian Public Listed Companies

Abstract: The objective of this study is to examine the determinants of Enterprise Risk Management (ERM) adoption in Malaysian Public Listed Companies (PLCs). The study focuses on ten industries from five hundred and seventy four Public Listed Companies in Malaysia for the period 2007. These ten industries include industrial products, trading/services, consumer products, properties, constructions, plantations, infrastructure projects, technology, hotels and mining. Logit regression approach will be employed, and a dummy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 5 publications
(9 reference statements)
2
43
2
3
Order By: Relevance
“…Since more diversified companies are faced with an increasing risk complexity, similar to company size, a positive relationship with ERM is assumed. The empirical results, however, cannot confirm this assumption in general, as only Razali et al (2011) find a positive significant relation for international diversification. Apart from that, the coefficients for (industrial and international) diversification are generally not significant and moreover negative with the exception of a positive relation for industrial diversification found in the insurance sample studied by Hoyt and Liebenberg (2011).…”
Section: Empirical Studies Of Erm Determinantsmentioning
confidence: 64%
See 4 more Smart Citations
“…Since more diversified companies are faced with an increasing risk complexity, similar to company size, a positive relationship with ERM is assumed. The empirical results, however, cannot confirm this assumption in general, as only Razali et al (2011) find a positive significant relation for international diversification. Apart from that, the coefficients for (industrial and international) diversification are generally not significant and moreover negative with the exception of a positive relation for industrial diversification found in the insurance sample studied by Hoyt and Liebenberg (2011).…”
Section: Empirical Studies Of Erm Determinantsmentioning
confidence: 64%
“…10 Hoyt and Liebenberg (2011) use the natural log of the stock returns' standard deviation, while Golshan and Rasid (2012) consider the difference of the year high and year low stock prices. 11 In Razali et al (2011), the measurement of (international) diversification (as a dummy variable)…”
Section: Empirical Studies Of Erm Determinantsmentioning
confidence: 99%
See 3 more Smart Citations